Policies of international friendship in judicial cooperation in criminal matters: the non-extradition of Brazilian and Portuguese nationals to third States: a comparison with EU Law = Políticas de amizade internacional na cooperação judiciária em matéria penal: a não-extradição de nacionais brasileiros e portugueses para terceiros Estados (comparação com o Direito da UE) - Costa, Miguel João (2019)
Submitted by betanial@stj.jus.br (betanial@stj.jus.br) on 2019-07-12T21:03:06Z No. of bitstreams: 2 polices_international_friendship_costa.pdf: 460988 bytes, checksum: 544e321709c27c285ebd12d13840ea49 (MD5) license.txt: 1239 bytes, checksum: c9b4c351324448672315a00808efb725 (MD5)